Developing community-based physical activity interventions and recreational programming for children in rural and smaller urban centres: a qualitative exploration of service provider and parent experiences - Emma Ostermeier; Jason Gilliland; Jennifer D. Irwin; Jamie A. Seabrook; Patricia Tucker (BMC, 2024)
Abstract Background Children's physical inactivity is a persisting international public health concern. While there is a large body of literature examining physical activity interventions for children, the unique physical activity context of low-density communities in rural areas and smaller urban centres remains largely underexplored. With an influx of families migrating to rural communities and small towns, evaluations of health promotion efforts that support physical activity are needed to ensure they are meeting the needs of the growing populations in these settings. The aim of this community-based research was to explore service providers' and parents' perspectives on physical activity opportunities available in their community and recommendations toward the development and implementation of efficacious physical activity programming for children in rural communities and smaller urban centres. Methods Three in-person community forums with recreation service providers (n = 37 participants) and 1 online community forum with the parents of school-aged children (n = 9 participants) were hosted. An online survey and Mentimeter activity were conducted prior to the community forums to gather participants' views on the barriers and facilitators to physical activities and suggestions for activity-promoting programs. The service provider and parent discussions were audio-recorded, transcribed verbatim, and analyzed following a deductive approach guided by Hseih and Shannon's (2005) procedure for direct content analysis. A code list developed from the responses to the pre-forum survey and Mentimeter activity was used to guide the analysis and category development. Results Seven distinct categories related to the existing physical activity opportunities and recommendations for programs in rural communities and smaller urban centres were identified during the analysis: (1) Recovery from Pandemic-Related Measures, (2) Knowledge and Access to Programs, (3) Availability, (4) Personnel Support, (5) Quality of Programs and Facilities, (6) Expenses and Subsidies, and (7) Inclusivity and Preferences. Conclusion To improve the health and well-being of children who reside in low-density areas, the results of this study highlight service provider and parent recommendations when developing and implementing community-based physical activity programs and interventions in rural and smaller urban settings, including skill development programs, non-competitive activity options, maximizing existing spaces for activities, and financial support.